Study of the Location and Morphology of the Pterion in Adult Nigerian Skulls. (12th June 2013) - Adejuwon, Sunday A.; Olopade, Funmilayo E.; Bolaji, Modupe
Abstract : The pterion which marks the union of 4 bones of the cranium is located superior to the zygomatic arch and posterior to the frontozygomatic suture. It is an important neurosurgical landmark for the lateral/pterional approach and has racial differences in both its location and pattern of union of the bones. This study aims to analyze the location and types of pterion in adult Nigerian skulls. Bilateral sides of 37 adult dry skulls were studied. The pterion types were classified; linear distances from the centre of the pterion to the midpoint of the zygomatic arch and to the frontozygomatic suture were measured; these were analyzed for side and gender differences. Sphenoparietal was the most common pterion type (86.1%) followed by frontotemporal (8.3%), stellate (5.6%), and epipteric types (0%). The mean distances from the pterion to the midpoint of zygomatic arch were39.74 ± 0.505 mm and37.95 ± 0.657 mm in males and females, respectively, while the distances to the frontozygomatic suture were31.87 ± 0.642 mm and30.35 ± 0.836 mm. The vertical position of the pterion was significantly higher in males than females. Bilateral occurrence is statistically insignificant. This information will be of neurosurgical and anthropological importance.